Thermal effect of a localized fire in the steel structure of an open car park - Piloto, P.A.G. (2020)
Due to the recent fíre events in open car parks and m order to increase the fire safety in this type of the building stmctures, simple calculation methods should be developed to estimate the thermal effects of a localized fire. This investigation deals with a parametric analysis, using different fire events (different car class), fíre scenarios (relative position ofthe car with respect to the main element of the stmcture and dimensions of the compartment) and section factor ofthe main supporting element ofthe structure (dimensions ofthe beam cross section). The temperature was calculated for each fíre scenario, around the beam (gás temperature) and also in the steel beam. The thermal effect on part of the stmcture was calculated by a mixed fonnulation, taking into consideration the Hasemi and Heskestad methods to evaluate the temperature of the gás and also the lumped thermal model for the calculation of the steel temperature.